RUSSIAN HISTORICAL SOCIETY AS AN ACTOR OF SYMBOLIC POLICY: INSTITUTIONAL FEATURES AND MEMORIAL RISKS - D. A. Anikin; A. Yu. Bubnov; A. V. Kompleev (Известия высших учебных заведений. Поволжский регион: Гуманитарные науки, 2020)
Background. The activities of modern non-governmental scientific and educational public organizations working in the field of comprehending the historical past have not yet been comprehensively studied in Russian science. The purpose of this study is to carry out a systematic analysis of the dynamics of the development of non-state actors of symbolic politics in modern Russia, especially the scientific public organization Russian Historical Society. Materials and methods. The study was conducted on the basis of documents and materials of the Russian Historical Society, published on the official website, in the informational publications of the company (Bulletin “Vorontsovo Field”). The work used materials from round tables, conferences, exhibitions, scientific publications and other projects of the Russian Historical Society. The methodological main research is the structuralist approach, which became the basis for distinguishing symbolic politics into a special type of political activity and a comparative analysis of sources that reveals the significance of this phenomenon for the development of modern Russian historical science. Results. The processes of the formation of various actors of symbolic politics in the recent history of Russia are described, the specifics and trends of their development are determined. An assessment is given of the main memorial projects of the Russian Historical Society in the space of symbolic politics in our country. Conclusions. The last twenty years have become a time of revitalization of symbolic politics in Russia. The dynamics of its development allows us to state that by 2012 the state, through its individual actors and institutions, has proceeded to actively formulate a public memorial agenda. At this time, the institutional formation of its non-state actors is taking place, among which the Russian Historical Society is becoming one of the most active. His activity focused on identifying the main vectors of historical research and articulating the historical and political agenda in the domestic political arena, while avoiding serious scandals and the traditional confrontation between supporters of the Soviet and anti-Soviet versions of history.